Functional Outcome, Recanalization, and Hemorrhage Rates After Large Vessel Occlusion Stroke Treated With Tenecteplase Before Thrombectomy. (30th November 2021) - Gerschenfeld, Gaspard; Smadja, Didier; Turc, Guillaume; Olindo, Stephane; Laborne, François-Xavier; Yger, Marion; Caroff, Jildaz; Gonçalves, Bruno; Seners, Pierre; Cantier, Marie; l'Hermitte, Yann; Aghasaryan, Manvel; et al.
Abstract : Background and Objectives: To investigate in routine care the efficacy and safety of IV thrombolysis (IVT) with tenecteplase prior to mechanical thrombectomy (MT) in patients with large vessel occlusion acute ischemic strokes (LVO-AIS), either secondarily transferred after IVT or directly admitted to a comprehensive stroke center (CSC). Methods: We retrospectively analyzed clinical and procedural data of patients treated with 0.25 mg/kg tenecteplase within 270 minutes of LVO-AIS who underwent brain angiography. The main outcome was 3-month functional independence (modified Rankin Scale score ≤2). Recanalization (revised Treatment in Cerebral Ischemia score 2b–3) was evaluated before (pre-MT) and after MT (final). Results: We included 588 patients (median age 75 years [interquartile range (IQR) 61–84]; 315 women [54%]; median NIH Stroke Scale score 16 [IQR 10–20]), of whom 520 (88%) were secondarily transferred after IVT. Functional independence occurred in 47% (n = 269/570; 95% confidence interval [CI] 43.0–51.4) of patients. Pre-MT recanalization occurred in 120 patients (20.4%; 95% CI 17.2–23.9), at a similar rate across treatment paradigms (direct admission, n = 14/68 [20.6%]; secondary transfer, n = 106/520 [20.4%]; p > 0.99) despite a shorter median IVT to puncture time in directly admitted patients (38 [IQR 23–55] vs 86 [IQR 70–110] minutes; p < 0.001). Final recanalization was achieved in 492 patients (83.7%; 95%CI 80.4–86.6). Symptomatic intracerebral hemorrhage occurred in 2.5% of patients (n = 14/567; 95% CI 1.4–4.1). Discussions: Tenecteplase before MT is safe, effective, and achieves a fast recanalization in everyday practice in patients secondarily transferred or directly admitted to a CSC, in line with published results. These findings should encourage its wider use in bridging therapy. Classification of Evidence: This study provides Class IV evidence that tenecteplase within 270 minutes of LVO-AIS increases the probability of functional independence.